2018
DOI: 10.1002/jat.3580
|View full text |Cite
|
Sign up to set email alerts
|

Binding affinity and decontamination of dermal decontamination gel to model chemical warfare agent simulants

Abstract: Six chemical warfare agent simulants (trimethyl phosphate, dimethyl adipate, 2-chloroethyl methyl sulfide, diethyl adipate, chloroethyl phenyl sulfide and diethyl sebacate) were studied in in vitro human skin to explore relationship between dermal penetration/absorption and the mechanisms of simulant partitioning between stratum corneum (SC) and water as well as between dermal decontamination gel (DDGel) and water. Both binding affinity to and decontamination of simulants using DDGel were studied. Partition co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 42 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…34 Chemicals’ binding affinities to SC protein/lipids are associated with their skin permeability. 35 As presented in Table 2 after 24 h of incubation, SC binding rate of 32 nm Fe 3 O 4 @SiO 2 was also four times of that of 33 nm SiO 2 . The results suggest that Fe 3 O 4 NPs have higher SC affinity than that of SiO 2 NPs.…”
Section: Discussionmentioning
confidence: 74%
“…34 Chemicals’ binding affinities to SC protein/lipids are associated with their skin permeability. 35 As presented in Table 2 after 24 h of incubation, SC binding rate of 32 nm Fe 3 O 4 @SiO 2 was also four times of that of 33 nm SiO 2 . The results suggest that Fe 3 O 4 NPs have higher SC affinity than that of SiO 2 NPs.…”
Section: Discussionmentioning
confidence: 74%
“…Frumet et al (2007) showed that maximal follicular contribution occurs with chemicals with intermediate Log P o/w values. Cao et al (2018) suggested that there is a little correlation between partitioning into SC and Log P o/w indication that SC is a less significant barrier for less lipophilic penetrants. Another study (Wu, Ramachandran, Weiner, & Roessler, 2001) suggested that actually sebaceous gland secretion could favor penetration of emulsions with higher lipophilicity.…”
Section: Discussionmentioning
confidence: 99%